A Fixed, Unreducible, Unstable Medial Swivel Dislocation of the Talonavicular Joint with Associated Navicular Fracture. (15th June 2021) - Layson, James T.; Afsari, Alan; Peterson, Todd; Knesek, David; Best, Benjamin
Abstract : A 32-year-old white male was on a second-story balcony when he fell off and landed on the cement below. With initial X-rays being read as negative on the radiology report due to the subtle nature of the injury, the patient was promptly diagnosed with a medial swivel dislocation by the orthopaedic team, which ended up being fixed, unstable, and irreducible. The patient also had acute skin compromise and needed to be taken to the operating room prior to progression of skin breakdown. This dislocation pattern is a rare variant, especially when paired with the fixed nature of the dislocation and the soft tissue compromise. In the end, open treatment was necessary in order to reduce the talonavicular joint. Because of early recognition and prompt treatment, skin breakdown was avoided. Internal screw fixation of the fractured navicular bone was needed along with K-wire insertion to hold the normal anatomy of the talonavicular joint reduced. All hardware was ultimately removed after healing, and anatomy was restored with excellent patient function. This case report highlights the orthopaedic knowledge needed to not only recognize this rare fracture-dislocation pattern but to also treat it promptly when encountered.